IMPLEMENTATION OF PRE-TRAINED DEEP LEARNING MODEL FOR DOG BREED CLASSIFICATION - et. al., Dr. DipeshG.Kamdar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Image classification made tremendous advancement with improved techniques and its accuracy continuously improves. However when comes to fine-grained classification, huge scope of improvement. It is easy to identify the various animals from the image, but not easy to identify the animal breed. In this paper, effort is made to improve the classification of animal breed. Standard Stanford dog breed dataset is used to train and test various pre-trained deep learning models. The effort is made to fine-tune pre-train network and compare the result.